Internationalization of Small and Medium-Sized Family Businesses During Crisis Time : A network approach - Agus Fernando (International Journal of Family Business Practices, 2022)
Network involvement and attitude factors influence the process of internationalization of small and medium family businesses. It is necessary to develop an operational and predictable framework to explain it in the era of globalization, which has an impact on small and medium enterprises, especially family businesses. This study offers a model consisting of network factors, attitudes, and global crises as factors that influence the level of the process of internationalization of small and medium family businesses. The findings from this study indicate that managerial attitude factors, namely trust relationships, market orientation, and international entrepreneurial orientation, are very important for the internationalization process. The global crisis, which is indicated by the existence of economic turbulence, increases during the crisis, but in the high turbulence group, it indicates that the influence of network involvement will also be stronger in the process of internationalization of small and medium family businesses. The findings of this study also have practical implications for family businesses, government organizations, and educational institutions.